The Importance of Social Media for Commerce. A Case Study in Madeira (Portugal) - Garcia Medina, Irene; Correia Pereira, Pedro Alvaro (International Journal of Interactive Mobile Technologies (iJIM), 2012)
The continuity and the success of organizations appear increasingly associated with the incorporation of social media. The success depends of the structural and procedural changes that the organization has to make. Today, social media are the new digital marketing tools that help in the processes of communication. Companies need to understand that they are no longer the exclusive owners of the relation of consumers with their products/services; instead, the survival of the organizations depends of the effective utilization of the social media. Creative and innovative solutions are not necessarily too expensive and the internet ends up being one of the best marketing tools available for the organizations. In a more transparent and dynamic world, consumers trust other people to provide advice and recommendations about products and services more and more through social media and it is important to know how and why social media influence organizations. This study analyzes through a literature review the current importance of social media for digital marketing communication and shows a case study on traditional shops that use social media to obtain competitive advantages over shopping centers in Funchal (Madeira, Portugal). To finish, the study proposes a new model of business for successful marketing strategies. Also, the article explains how to manage the changes associated and how collaborators need to get used to working in a wider and more dynamic community.